2011
DOI: 10.1645/ge-2701.1
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Ctenocephalides canis (Curtis) and Ctenocephalides felis (Bouché) Infesting Dogs In the City of Aguascalientes, México

Abstract: Prevalence and seasonal distribution of Ctenocephalides canis (Curtis) and Ctenocephalides felis (Bouché) infestations in urban dogs of the city of Aguascalientes, Mexico, were studied. Between January and December 2007, 863 dogs in the Municipal Canine and Feline Control Center were examined. Overall prevalence of infestation was 12% (95% CI 10-14). Seasonal distribution revealed that prevalences in spring and summer were highest, while autumn and winter had lower prevalences. Two infestation peaks were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
2
4
1
6
Order By: Relevance
“…It could be noted the presence of the pronatal comb (with six spines for both species), as well as the rounded margin in the case of C. canis; however, the head has a longer and more pronunced angle in C. felis. It is notably to highlight that the two species were found as mixed infestation in the studied dogs; however, C. felis was the most prevalent flea (Table 1), as stated by Beugnet et al 4 In the scientific literature, there are reports of mixed infections by C. canis and C. felis, 11,15,17 similar to the observations in our study, were all the positive dogs presented infestation of at least one specimen of both species. It is known that the presence of C. canis has more restricted geographic distribution, and that the presence of C. felis has increased, even displacing C. canis, from which the reasons are not well.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…It could be noted the presence of the pronatal comb (with six spines for both species), as well as the rounded margin in the case of C. canis; however, the head has a longer and more pronunced angle in C. felis. It is notably to highlight that the two species were found as mixed infestation in the studied dogs; however, C. felis was the most prevalent flea (Table 1), as stated by Beugnet et al 4 In the scientific literature, there are reports of mixed infections by C. canis and C. felis, 11,15,17 similar to the observations in our study, were all the positive dogs presented infestation of at least one specimen of both species. It is known that the presence of C. canis has more restricted geographic distribution, and that the presence of C. felis has increased, even displacing C. canis, from which the reasons are not well.…”
Section: Resultssupporting
confidence: 89%
“…Our results are in agreement with the report of Beugnet et al 4 who mentioned that in the domestic dog the most prevalent flea species around the world is C. felis. In our study, the prevalence observed for C. felis was of 92%, surpassing the 38% reported by Hernández-Valdivia et al 11 in Aguascalientes, México; as well as the 46.4% reported by Orozco-Murillo et al 17 in Valle de Aburrá, Colombia, and the 16.3% reportead by Rinaldi et al 15 in Campania, Italia. The obtained prevalence in this study (2.3%) with respect to C. canis, contrasts with the report of Nuchjangreed and Somprasong, 18 in Pattaya, district of Thailand, where they found this flea species in 11.7% of the examined dogs; while Jafari-Sohoorijeh et al 19 in Shiraz, Iran, reported a prevalence of 13.7%, and Cruz-Vázquez et al 10 in Cuernavaca, Morelos a total of 16.8% of C. canis in infested dogs respectively.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…Ctenocephalides canis (Curtis, 1826) AGUASCALIENTES: Aguascalientes: Canis lupus familiaris (Hernández-Valdivia et al 2011). No specimens in collections.…”
Section: Phylum: Arthropoda Von Siebold 1848mentioning
confidence: 99%